The Regulation of SPRY4 Intronic Transcript 1 (SPRY4-IT1) on KIT Signaling and Imatinib Resistance of Gastrointestinal Stromal Tumor (GIST) Cells - Yuanyuan Yu; Zongying Jiang; Sien Zhao; Cuiyun Liu; Jinhai Ma; Shujing Li (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: SPRY4 intronic transcript 1 (SPRY4-IT1), is a long non-coding RNA coded by the intron of SPRY4. SPRY4 is highly expressed in gastrointestinal stromal tumor (GIST) and inhibits the tumorigenesis of GIST, but whether SPRY4-IT1 regulates the tumorigenesis of GIST or not remains unclear. Therefore, in this study, the regulation of SPRY4-IT1 expression and its role in GIST will be investigated.METHODS: GIST-T1 cells, and Ba/F3 cells which express KIT proto-oncogene (KIT) and SPRY4-IT1 were used as cell models. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) was used to examine mRNA expression, while the protein expression and signal transduction were examined by western blot. The association between SPRY4-IT1 and KIT was examined by pull down of KIT and PCR. Cell proliferation, survival, and cell cycle progression were examined by cell counting kit-8 (CCK8) and flow cytometry.RESULTS: KIT mutants increased the expression of SPRY4-IT1 in GIST. SPRY4-IT1 bound to KIT, also enhanced the activation and expression of both wild-type KIT and primary KIT mutants, therefore increasing the activation of downstream signaling proteins AKT and ERK of KIT, GIST cell survival, and proliferation. In addition, SPRY4-IT1 reduced the sensitivity of wild-type KIT, or primary KIT mutants to the first-line targeted therapeutic drug of GIST, imatinib, which can inhibit KIT activation. Gaining drug-resistant secondary KIT mutants might be one of the main reasons of GIST recurrence after targeted therapy. Similar to wild-type KIT and primary KIT mutants, the activation and expression of secondary KIT mutants and their resistance to imatinib were also increased by SPRY4-IT1.CONCLUSION: The results indicated positive feedback between SPRY4-IT1 and wild-type KIT, primary KIT mutants or secondary KIT mutants, and the upregulation of AKT and ERK activation by SPRY4-IT1 in GIST cells, providing a new insight in the KIT signaling regulation in GIST, and the resistance of GIST to targeted therapy.KEYWORDS: SPRY4-IT1, KIT, GIST, SPRY4, signaling